Filth flies associated with municipal solid waste and impact of delay in cover soil application on adult filth fly emergence in a sanitary landfill in Pulau Pinang, Malaysia. Issue 3 (10th January 2013) - Nurita, A.T.; Hassan, A. Abu
Abstract: Two types of municipal solid waste (MSW), newly arrived and 2 weeks old, were sampled from a sanitary landfill in Pulau Pinang, Malaysia at a fortnightly interval and kept under field conditions for 2 weeks. A total of 480 kg of each type of MSW was sampled to study species composition and impact of delays in cover soil applications on filth fly emergence. Out of 960 kg of MSW sampled, 9.2 ± 0.5 flies emerged per kilogram. Weekly adult fly emergence rates of newly arrived and 2-week-old waste did not differ significantly and MSW remained suitable for fly breeding for up to 1 month. Eight species of flies emerged from the MSW: namely, Musca domestica, Musca sorbens, Synthesiomyia nudiseta, Hydrotaea chalcogaster, Chrysomya megacephala, Lucilia cuprina, Hemipyrellia ligurriens and Sarcophaga sp. Newly arrived waste was determined to be the main source for M. domestica, C. megacephala and L. cuprina in the landfill owing to significantly higher mean emergence compared with 2-week-old waste. Musca sorbens was found in newly arrived waste but not in 2-week-old waste, suggesting that the species was able to survive transportation to landfill but unable to survive landfill conditions. Hemipyrellia ligurriens, H. chalcogaster and S. nudiseta were not imported into the landfill with MSW and pre-existing flies in and around the landfill itself may be their source. The results show that landfills can be a major source of fly breeding if cover soil or temporary cover is not applied daily or on a regular schedule.